Groups process and practice - Corey, Marianne Schneider 1942-; Corey, Gerald; Corey, Cindy (Cengage Learning Asia Pte Ltd, 2018)
Drawing on their extensive clinical experience in working with groups, Marianne, Gerald, and Cindy Corey provide a realistic approach to the blending of theory with practice in group work. Offering up-to-date coverage of both the what is and the how to of group counseling, the tenth edition incorporates the latest research, ethical guidelines, and practices to ensure student success in the classroom and beyond. The authors revised the book with instructors and students in mind, emphasizing personal and interactive learning. New features make an instructor's job easier, providing a range of ways to teach and appealing to a variety of learning styles. Many new activities within the chapters have broad application, both for in-class learning as well as in work settings with diverse clients.